Case management for older women experiencing homelessness in Australia: a sustaining tenancies model of housing and support - Watson, Juliet; Martin, Robyn; Haylett, Freda (Frontiers in Global Women's Health, 2025)
This community case study examines the efficacy of the Women's Housing Support Program (WHSP), which provides case management to older women experiencing homelessness in Melbourne, Australia. In recent years there has been an increase in the number of older women experiencing homelessness in Australia. Some have experienced long-term, chronic homelessness, but there has also been an escalation in homelessness for women who have previously led conventional lives before a significant event such as relationship breakdown, loss of employment, or health crisis results in poverty that contributes to homelessness. The circumstances of older age, gender, and homelessness mean that some older women require specialised responses to access suitable long-term housing and to receive appropriate support that will stabilise their housing. This case study explores the distinctive social, health, and housing needs of women accessing the WHSP and considers how the sustaining tenancies model of support responds to these needs. Based on a mixed-methods study that included interviews with service users, case managers, senior managers, and an external service provider, as well as program data analysis, the case study indicates that older women benefit from specialised support that focuses on housing for life, health care, emotional support, and digital literacy. Additionally, in order to facilitate successful outcomes, this support needs to be flexible, client-centred, and trauma-informed.